The effects of menstrual cycle-based aerobic training on resting metabolism and maximal oxygen uptake and the associations of energy availability to the adaptations - Harju, Tilda (2025)
Introduction. The fluctuating female sex hormones, primarily estrogen and progesterone, affect several physiological functions differently across the menstrual cycle phases. These changes may further influence athletic performance. Due to this, the concept of training according to an individual’s menstrual cycle has gained interest. However, the adaptations to menstrual cycle-based aerobic training have not been explored extensively. The purpose of the present study was to investigate the effects of menstrual cycle-based moderate intensity exercise training (MIET) on resting metabolic rate (RMR) and maximal oxygen uptake (VO2max). Additionally, the study aimed to explore the associations between energy availability (EA) and the possible training adaptations in RMR and VO2max.